TRADISI PEMBERIAN UANG MASUK KAMAR DALAM PERSPEKTIF HUKUM ISLAM (Studi Kasus Pernikahan Dalam Masyarakat Nagari Taluak Tigo Sakato Kecamatan Batang Kapeh Kabupaten Pesisir Selatan) - Duhriah Duhriah; Suhaila Ulfa (Jurnal AL-AHKAM, 2021)
This study was initiated by the discovery of many people's habits of carrying out a tradition after marriage, known as the giving of room-entry money, which was carried  out  in  Kenagarian  Taluak  Tigo  Sakato,  Batang  Kapeh  District.  The research questions in this study are. First, how is the implementation of the money- in-room  tradition  in  Kenagarian  Taluak  Tigo  Sakato,  Batang  Kapeh  District, Pesisir Selatan Regency. Second, what is the impact of not fulfilling the tradition of giving money into the room. Third, what is the public's view of the tradition of giving money into the room. Fourth, how is the review of Islamic law on the provision  of  money  into the room. This type of  research  is a field research  by collecting  the  results  of  interviews  with  men,  ninik  mamak,  families  who  are present in the implementation of this tradition. The results of this study are: first, the implementation of the tradition of giving room entry money in Kenagarian Taluak Tigo Sakato, Batang Kapeh District, is carried out at the bride's house which is handed over by the man to the woman after the marriage contract is carried out. The second impact of not fulfilling the tradition of giving money into the room is that the groom is not allowed to enter the bridal chamber. The three public responses to the tradition of giving money into the room have positive and negative responses. The positive response is that the people in Kenagarian Taluak Tigo Sakato support and accept this tradition of giving money to the room rather than being ostracized by the community. While the negative response is that there are people who object to the tradition of giving money into this room but they still do it with a heavy heart. The fourth review of Islamic law on the provision of room entry  fees  is  urf  sahih  because  it  does  not  conflict  with  religion  and  aims  to maintain the benefit of society